Characteristics and mechanism of electrochemical peroxymonosulfate activation by a Co–N@CF anode for pollutant removal. Issue 1 (22nd November 2021) - Lin, Ping; Zhu, Weihuang; Gao, Ying; Li, Junli; Liu, Jiawu; Zhang, Jianfeng; Huang, Tinglin
Abstract : Herein, carbon felt (CF) modified with N and Co (Co–N@CF) was prepared as an anode to effectively activate peroxymonosulfate (PMS) for tetracycline (TC) removal. Abstract : Herein, carbon felt (CF) modified with N and Co (Co–N@CF) was prepared as an anode to effectively activate peroxymonosulfate (PMS) for tetracycline (TC) removal. The influencing factors, kinetic characteristics and the transformation of generated active radicals were further investigated. The results show that N and Co modification of CF via a galvanostatic electrodeposition method results in a significant decrease in the charge transfer resistance ( R ct ) of the CF. The fabricated Co–N@CF anode exhibits high catalytic performance and stability towards PMS activation, wherein the TC removal efficiency reached 92.2% within 1 h under optimal conditions. Radical quenching tests and electron paramagnetic resonance spectroscopy experiments demonstrated that SO4 ˙ −, OH˙ and O2 ˙ − are the main contributors towards TC removal, while 1 O2 generation is inhibited significantly. The PMS decomposition process driven by the activator enhances the generation of OH˙. The electricity energy demand per order (EE/O) in the reaction system (Co–N@CF anode + PMS) is only 0.072 kWh m −3, which makes it an energy-saving approach for pollutant removal. The newly developed fabrication of the Co–N@CF anode for PMS activation could provide insights into the SO4 ˙ − -based electrochemical advanced oxidation process (EAOP) applied in wastewater treatment.